Comparing Miniopen and Minimally Invasive Transforaminal Interbody Fusion in Single-Level Lumbar Degeneration. (5th January 2015) - Lo, Wei-Lun; Lin, Chien-Min; Yeh, Yi-Shian; Su, Yu-kai; Tseng, Yuan-Yun; Yang, Shun-Tai; Lin, Jai-Wei
Abstract : Degenerative diseases of the lumbar spine, which are common among elderly people, cause back pain and radicular symptoms and lead to a poor quality of life. Lumbar spinal fusion is a standardized and widely accepted surgical procedure used for treating degenerative lumbar diseases; however, the classical posterior approach used in this procedure is recognized to cause vascular and neurologic damage of the lumbar muscles. Various studies have suggested that using the minimally invasive transforaminal interbody fusion (TLIF) technique provides long-term clinical outcomes comparable to those of open TLIF approaches in selected patients. In this study, we compared the perioperative and short-term advantages of miniopen, MI, and open TLIF. Compared with open TLIF, MI-TLIF and miniopen TLIF were associated with less blood loss, shorter hospital stays, and longer operative times; however, following the use of these procedures, no difference in quality of life was measured at 6 months or 1 year. Whether miniopen TLIF or MI-TLIF can replace traditional TLIF as the surgery of choice for treating degenerative lumbar deformity remains unclear, and additional studies are required for validating the safety and efficiency of these procedures.